Syncope associated with pain as the presenting feature of neck malignancy: failure of cardiac pacemaker to prevent attacks in two cases. Issue 9 (16th August 2005) - Worth, P F; Stevens, J C; Lasri, F; Brew, S; Reilly, M M; Mathias, C J; Rudge, P
Abstract : Two patients are described in whom syncope was the presenting clinical feature of an undiagnosed neck malignancy. Both patients also had attacks associated with paroxysms of severe neck pain. Neither patient responded to cardiac pacing.